Komiškasis kalbos raiškumas J. Erlicko "Knygoje" - Simsonaitė, Beatričė (Respectus Philologicus, 1999)
The purpose of this work is to discuss some of the linguistic means that produce comic effects in J. Erlickas’ prize-winning novel "The Book". These effects are achieved primarily through semantic and syntactic means. Homophonic and semantic puns, illogicality, and irony characterize this work’s rich texture. Particularly innovative is Erlickas’ contamination or interanimation of two entirely logical word combinations so as to create a hybrid that is patently illogical: brilliant and original nonsense.